Incidence of bladder cancer in a cohort of workers exposed to 4-chloro-o-toluidine while synthesising chlordimeform. Issue 8 (August 1992) - Popp, W; Schmieding, W; Speck, M; Vahrenholz, C; Norpoth, K
Abstract : Between 1982 and 1990 seven cases of bladder cancer were detected in a group of 49 workers who were synthesising chlordimeform from 4-chloro-o-toluidine. Latency periods ranged from 15 to 23 years. The incidence of bladder tumours in this group was significantly higher than that of the cancer registers of the former GDR, Saarland, and Denmark by factors of 89.7, 53.8, and 35.0 respectively. This provides further evidence that monocyclic aromatic amines such as 4-chloro-o-toluidine may be carcinogenic in humans.